2015
DOI: 10.1109/thms.2014.2362529
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Activity Transitions for Prompting

Abstract: Individuals with cognitive impairment can benefit from intervention strategies like recording important information in a memory notebook. However, training individuals to use the notebook on a regular basis requires a constant delivery of reminders. In this work, we design and evaluate machine learning-based methods for providing automated reminders using a digital memory notebook interface. Specifically, we identify transition periods between activities as times to issue prompts. We consider the problem of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Therefore, any supervised learning algorithm that generates an interpretable model (such as a decision tree or a rule learner) will not only identify a change but also describe the nature of the change. Support vector machines [21][40], naïve Bayes [21], and logistic regression [21] have been tested using this approach. This type of problem will also suffer from extreme class imbalance as there are typically many more within-state sequences than change point sequences.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, any supervised learning algorithm that generates an interpretable model (such as a decision tree or a rule learner) will not only identify a change but also describe the nature of the change. Support vector machines [21][40], naïve Bayes [21], and logistic regression [21] have been tested using this approach. This type of problem will also suffer from extreme class imbalance as there are typically many more within-state sequences than change point sequences.…”
Section: Reviewmentioning
confidence: 99%
“…In a time series, using sliding window X t as a sample instead of x t , an interval χ t with Hankel matrix { X t , X t +1 , … , X t + n –1 } as shown in Figure 2 will be a set of n retrospective subsequence samples starting at time t [2][21][22]. …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we developed an activity recognition algorithm that has the ability to detect transitions and deliver prompts automatically during activity transitions, thus eliminating the need for human intervention [36]. In a separate study, we evaluated detection of transition periods in scripted and unscripted environments and found that the recognition algorithm was able to detect transition periods greater than 80% of the time, with a false positive rate of less than 15% [37]. However, our completed prompting system would require users to have infrared motion sensors installed in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques have been proposed for this task. Some approaches are unsupervised and utilize object-use fingerprints [64], [65] or statistical change point detection [66], [67]. …”
Section: Related Workmentioning
confidence: 99%